Elaboración de una Guía Gastronómica de la Ciudad de Salcedo Provincia de Cotopaxi periodo 2018- 2019. - Gavilánez Ponce, Marcela Jacqueline (2019)
The present study focused on the development of a gastronomic guide for Salcedo's caregiver, which was executed through the collection of primary and secondary information where the current situation of the study area was analyzed through the situational diagnosis based on three elements: socio-economic, cultural and environmental diagnosis, it will be determined that in the caretaker of Salcedo the main activity to generate economic income is livestock that stands out with a 26.24% percentage. The Salcedo canton is composed of 6 urban and 5 rural parishes in which the Matriz San Miguel parish has the majority of the population men with 47.89% while women with 52.11%. In addition, it lacks valleys, plains, hills and its climate ranges are between 13 and 20 degrees. In order to know the number of dishes and gastronomic processes of the city, an inventory was carried out by applying the INPC files, resulting in 17 gastronomic processes of which 14 affected the daily gastronomy and 3 the festive gastronomy. As a final objective, the information was organized to design a gastronomic guide for Salcedo for the recovery and dissemination of intangible cultural heritage facing the new market trends and for the low transmission of recipes through the generation’s orality.